Atypical juvenile histiocytosis with novel KIF5B-ALK gene fusion mimicking subglottic hemangioma. (November 2019) - Wolter, Nikolaus E.; Ngan, Bo; Whitlock, James A.; Dickson, Brendan C.; Propst, Evan J.
Abstract: Juvenile Xanthograuloma (JXG) is part of a diverse set of rare histiocytic disorders marked by infiltration of tissues with neoplastic myelomonocytic-derived cells. Molecular analysis has yielded new insights into the classification and management of histiocytic diseases. A three-year-old presented with atypical croup due to a localized subglottic histiocytic lesion mimicking subglottic hemangioma. The lesion was removed via tracheofissure. Pathology revealed a JXG-like histopathology with a rare KIF5B-ALK fusion gene. This is the first isolated ALK-positive lesion to be reported in this location. The discovery of the new ALK-positive subclass of histiocytosis has opened the door for targeted monoclonal ALK inhibition.